2019
DOI: 10.1111/1462-2920.14734
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities across nearshore to offshore coastal transects are primarily shaped by distance and temperature

Abstract: Summary Recent studies have focused on linking marine microbial communities with environmental factors, yet, relatively little is known about the drivers of microbial community patterns across the complex gradients from the nearshore to open ocean. Here, we examine microbial dynamics in 15 five‐station transects beginning at the estuarine Piver's Island Coastal Observatory (PICO) time‐series site and continuing 87 km across the continental shelf to the oligotrophic waters of the Sargasso Sea. 16S rRNA gene lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 48 publications
10
57
1
Order By: Relevance
“…We found that seasonality overwhelmed spatial variability of bacterial community composition. In contrast, at the similar spatial scale, the spatial variability dominated patterns were found across a river-to-ocean gradient in the Columbia River margin [ 14 ] and along a nearshore-to-offshore gradient in the Sargasso Sea [ 10 ], corresponding to the stronger environmental gradients over space (salinity in the former and water temperature in the latter) compared with those in this work. Here, the strong seasonal succession in bacterioplankton could be due to the strong seasonal changes in water temperature and DO concentration.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…We found that seasonality overwhelmed spatial variability of bacterial community composition. In contrast, at the similar spatial scale, the spatial variability dominated patterns were found across a river-to-ocean gradient in the Columbia River margin [ 14 ] and along a nearshore-to-offshore gradient in the Sargasso Sea [ 10 ], corresponding to the stronger environmental gradients over space (salinity in the former and water temperature in the latter) compared with those in this work. Here, the strong seasonal succession in bacterioplankton could be due to the strong seasonal changes in water temperature and DO concentration.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we tested two biogeographic patterns: (i) covariation of community composition and distance to shore (land) (Pattern I) and (ii) distance–decay relationship (Pattern II). Wang et al found significant Pattern I in the Sargasso Sea by integrating data from many different months for years [ 10 ], but the existence of seasonality was not concerned. In our work, seasonal consistency in Pattern I was evidenced by significant correlation between DTL and PCoA 1 and 2 coordinates in the summer, autumn, and winter, but the spatial turnover of bacterial communities in the spring did not fit Pattern I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations